Potensi Memajukan Perekonomian Desa Sukamaju Rancakalong Sumedang Melalui OVOP Jarenju - Purwadhi (Bandung Conference Series: Economics Studies, 2024)
Abstract. It is recorded that in 2023, Sukamaju Village, Rancakalong District, Sumedang Regency has 4,622 total inhabitants, the productive land area is rice fields and agriculture, and one of the other potentials is to have a palm starch factory with 7 factory locations with an estimated production of 10 tons of palm sugar per month. With the background of the initiative to maintain and promote ginger farming, where these crops constitute the majority of commodities from Sukamaju Village, the concept of One Village One Product (OVOP) needs to be encouraged. Jarenju is a superior product that stands for "Jahe Aren Sukamaju". The results of this community service activity involving students and the lecturer team, in the form of extracting product potential, making packaging designs, analyzing production costs, and training in making Jarenju which are expected to improve the village economy. Abstrak. Tercatat pada tahun 2023, Desa Sukamaju Kecamatan Rancakalong Kabupaten Sumedang memiliki sebanyak 4.622 jumlah penduduk, luas tanah produktif adalah pesawahan dan pertanian, dan salah satu potensi lainnya yakni memiliki pabrik pati aren dengan jumlah 7 lokasi pabrik dengan perkiraan menghasilkan 10-ton gula aren per bulan. Dengan latar belakang dari inisiatif ingin mempertahankan dan mengangkat hasil tani jahe, dimana hasil tani ini merupakan mayoritas komoditi dari Desa Sukamaju, maka konsep One Village One Product (OVOP) perlu didorong. Jarenju adalah produk unggulan yang merupakan singkatan dari "Jahe Aren Sukamaju". Hasil dari kegiatan pengabdian yang melibatkan mahasiswa dan tim dosen pengampu ini berupa penggalian potensi produk, pembuatan desain kemasan, analisis biaya produksi, dan pelatihan pembuatan Jarenju yang diharapkan dapat meningkatkan ekonomi desa.